Comparison Between I-Gel And Endotracheal Tube For Peak Airway Pressure During General Anesthesia In Pediatric Inguinal Hernia Surgeries - Raza, Muhammad Ahmed; Yasin, Bilal; Humayun Munir Tarar; Hussain, Mansoor; Saleem, Muhammad Muzzamal; kakar, Abdullah Sher (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare I-gel and Endotracheal tube for peak airway pressure during general anesthesia in pediatric inguinal hernia surgeries Study Design: Quasi experimental study. Place and Duration of Study: Anesthesia/surgical department, Pak Emirates Military Hospital Rawalpindi, Pakistan Jun to Nov 2021. Methodology: A Quasi experimental study was conducted on 250 children. Patients were randomly assigned into two groups. Group-A received the I-gel after induction with sedative agents while Group-B received the Endotracheal tube with routine induction and muscle paralysis. Peak airway pressure was monitored by the consultant anesthetist on anesthesia workstation throughout the surgery. Results: Out of 250 pediatric patients undergoing hernia repair randomized into two groups, 136(54.4%) were categorized into Group-A and 114(45.6%) were categorized into Group-B. Mean age of patients in our study was 3.35±2.454 years. 159(63.6%) children included in the study were male while 91(36.4%) were female. Out of 250, 202(80.8%) patients had normal peak airway pressure during the surgery while 48(19.2%) had raised pressure during the surgery. Use of Endotracheal tube was found statistically significantly associated with raised peak airway pressure during the surgery (p-value<0.05). Conclusion: Use of I-gel was found better in relation to maintenance of peak airways pressure as compared to Endotracheal tube in pediatric patients undergoing hernia repair under general anesthesia.